International Quasi-Constitutionalism and Corporate Citizenship: Language, Troubles, Dilemmas - Thompson, Grahame (HERMES - Journal of Language and Communication in Business, 2009)
Why are companies increasingly adopting the language of ‘citizenship’ to describe themselves? This is the issue taken up in this article. It is suggested the claims and forms of address in respect to ‘global corporate citizenship’ are part of wider governance moves in the international system, associated with a certain constitutional terminology and moves to progressively juridicalize the international arena. The article explores the forms of these moves as regards company activity in particular, and illustrates the difﬁcult consequences of the processes being described from the point of view of traditional international law and corporate governance.